2021
DOI: 10.21203/rs.3.rs-346581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcitriol Exerts Prophylactic Anti-Mycobacterium Effect In A Dose-Dependent Manner

Abstract: Vitamin D was empirically applied for Tuberculosis (TB) treatment in the past, and is currently used as an adjuvant for TB therapy. Although an increasing pile of evidences suggests that vitamin D has no therapeutic effect against TB infection, the prophylactic effect of vitamin D in preventing TB remains largely undetermined. To experimentally valuate the potential prophylactic effect of calcitriol (the active form of vitamin D) against mycobacterium infection, we performed dose-gradient calcitriol soaking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It was proved by a significant decrease in tissue MDA and TNF-α levels and a significant increase in tissue TAC in the CH group as compared to the CL group. These results agree with Kianian et al, (2019) 77 and Li et al, (2021) 78 .…”
Section: Discussionsupporting
confidence: 93%
“…It was proved by a significant decrease in tissue MDA and TNF-α levels and a significant increase in tissue TAC in the CH group as compared to the CL group. These results agree with Kianian et al, (2019) 77 and Li et al, (2021) 78 .…”
Section: Discussionsupporting
confidence: 93%
“…The observation that DPI adjunct to ATT cleared the spleen of bacterial burden indicates that calcitriol administered in the form of soluble inhaled particles was systemically absorbed rapidly. Exposing zebra fish infected with Mycobacterium marinum to a high dose of calcitriol (2500 µg/L/day) for 30 days led to significant reduction in bacterial burden; whereas low and medium doses (25 and 250 µg/L/day) showed minimal and no reduction respectively [34]. Another study by Crowle et al demonstrated that calcitriol at concentration 4 µg/ml (supraphysiological, approximately 5 log greater than normal circulating levels) in vitro was able to increase the doubling time of intracellular Mtb but had no significant bactericidal activity [12].…”
Section: Colony Countmentioning
confidence: 98%